Colonial Representation of Kipling’s The Man Who Would Be King : Theme Analysis - Wahyu Indah Mala Rohmana; Fitri Pangestu Noer Anggrainy (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2022)
This paper aims to discover the representation of colonialism in literary work “The Man Who Would Be King” written by Rudyard Kipling. This paper uses descriptive qualitative in analyzing the collected data. In this study, the writer used four characteristics to find the colonialism theme. It is found that the theme presented in thoughts and conversation of the main characters affects the event of the story. This study reveals that the cause of colonialism in the story is the dominant power hierarchy of the Colonizer. The superstition of being White also makes the colonizer feel superior than its subjugates. The representation of colonialism also shown when the Native is considered as primitive and uncivilized, while the Colonizer is narrated for being more modern and have more power.